Tahlil Kitab Ta’lim al-Lughah al-Arabiyyah “Äl-Arabiyyah baina Yadai Auladina” min Mandhur Amani wa Awatif / Analysis of the Book of Ta’lim al-Lughah al-Arabiyyah “Äl-Arabiyyah baina Yadai Auladina” From the Perspective of Amani and Awatif - Nais Musyafaul Faiza (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
This research was conducted to obtain an overview of the quality of the Arabic language textbook Al Arabiyyah Baina Yadai Auladina Volume I by Abdurrahman bin Ibrahim Al Fawzan and Muhammad bin Abdurrahman Al Syaikh. The analysis was carried out using an assessment instrument according to Amani and Awatif which includes five things, namely: introduction to the book, overall quality of the book, quality of book contents, activities and learning media, quality of assessment methods. Primary data sources were obtained from book analysis activities, while secondary data came from published scientific literature which was in line with the research conducted. This paper is a type of qualitative research that attempts to interpret and give meaning to the facts and information being researched. The results of the research obtained the following data: the introductory aspect of the book received a score of 2.7; the overall quality aspect of the book gets 3.8 points; quality aspect of book content 3.0; in terms of activities and learning media, score 3.25; then the quality of the assessment method is 3.0.أُجري هذا البحث للحصول على تصور لجودة كتاب تعليم اللغة العربية "العربية بين يدي أولادنا" الجزء الأول لمؤلفيه عبد الرحمن بن إبراهيم الفوزان ومحمد بن عبد الرحمن الشيخ. أُجري التحليل باستخدام أداة تقييم وفقًا لمنظور أماني وعواطف، والتي تشمل خمسة جوانب: مقدمة الكتاب، الجودة الكلية للكتاب، جودة محتوى الكتاب، الأنشطة ووسائل التعلم، وجودة أساليب التقييم. اُشتقت مصادر البيانات الأولية من أنشطة تحليل الكتاب، بينما جاءت البيانات الثانوية من الأدبيات العلمية المنشورة التي تتوافق مع البحث المُجرى. يُصنف هذا البحث ضمن الأبحاث النوعية التي تسعى لتفسير وإعطاء معنى للحقائق والمعلومات قيد الدراسة. أظهرت نتائج البحث البيانات التالية: حصل جانب مقدمة الكتاب على 2.7 نقطة؛ وحصل جانب الجودة الكلية للكتاب على 3.8 نقطة؛ وحصل جانب جودة محتوى الكتاب على 3.0 نقطة؛ أما جانب الأنشطة ووسائل التعلم فحصل على 3.25 نقطة؛ وجودة أساليب التقييم على 3.0 نقطة.